2021
DOI: 10.1177/00113921211007153
|View full text |Cite
|
Sign up to set email alerts
|

Risk, mourning, politics: Toward a transnational critical conception of grief for COVID-19 deaths in Iran

Abstract: This article examines the case of COVID-19 deaths and grief in Iran in order to shed light on how the biological, social and political ‘risks of contagion’ combine to impact mourning and grief. As a contagious biological agent, the novel coronavirus causes people to suffer, die and grieve alone. But this loneliness is deepened due to social stigma and political abandonment. Conceptually guided by Mary Douglas’s work on the socio-cultural and political constructions of ‘contagion’, Judith Butler’s notion of ‘un… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
10
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(11 citation statements)
references
References 24 publications
0
10
0
1
Order By: Relevance
“…Families in the current study who felt incomplete due to not being able to give their family member the proper funeral rituals shared a sense of guilt similar to that of bereaved families in the UK (Lightbody et al, 2022 ). In other studies, such disrupted bereavement and grieving processes were found to be associated with prolonged grief symptoms because the final memory of a loved one might become distorted (Bayatrizi et al, 2021 ; Djelantik et al, 2021 ; Gabay & Tarabeih, 2022 ; Smith et al, 2022 ).…”
Section: Discussionmentioning
confidence: 92%
See 4 more Smart Citations
“…Families in the current study who felt incomplete due to not being able to give their family member the proper funeral rituals shared a sense of guilt similar to that of bereaved families in the UK (Lightbody et al, 2022 ). In other studies, such disrupted bereavement and grieving processes were found to be associated with prolonged grief symptoms because the final memory of a loved one might become distorted (Bayatrizi et al, 2021 ; Djelantik et al, 2021 ; Gabay & Tarabeih, 2022 ; Smith et al, 2022 ).…”
Section: Discussionmentioning
confidence: 92%
“…In light of this finding, a previous study noted that spiritual healers and religious leaders are an important part of Indonesian culture and belief systems (Liem, 2020 ). Previous studies among Muslims in Iran (Bayatrizi et al, 2021 ) and Jews in the US (Dajani et al, 2022 ) also highlighted the importance of engaging religious leaders in communicating the COVID-19 funeral protocol to bereaved families. These religious leaders are trusted by the community and can be helpful if modification of the funeral rites and rituals is needed (Suwalowska et al, 2021 ), and they can also provide pastoral care to the bereaved families (Gulo et al, 2022 ; Lightbody et al, 2022 ).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations